Spatial Variation of heavy metal Pollution on road surfaces from Traffic sources in University of Nigeria, Enugu campus - Ichu; Chigozie Bright; Emeagi, Henry Okechukwu (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
This study aims to analyze heavy metal concentrations on road deposited sediment (RDS) using the road network within Enugu Campus of University of Nigeria, (UNEC) as a study site. RDS samples were collected at two transverse positions from different sites within a week in order to describe the influence of traffic on heavy metal emissions. The heavy metal concentrations of the RDS were determined by strong tri-acid digestion and atomic absorption spectrometry. The mean concentrations for Co, Mn, Zn, Ni and Fe were found to be 11.53, 99.92, 221, 44.23 and 216 mg kg-1 from samples near the curb and 12.37, 92.25, 248.87, 43.62 and 197.5 mg kg-1 from samples 1 m from the curb respectively. The mean electrical conductivity (EC), pH and total organic matter (TOM) were found to be 304μS/cm, 7.13, and 6.9% from samples near the curbS/cm, 7.13, and 6.9% from samples near the curb and 408μS/cm, 7.13, and 6.9% from samples near the curbS/cm, 7.33 and 5.57% 1 m from the curb, respectively. The results of the geochemical models: contamination factor (degree of contamination and enrichment factor agree to a very high level of contamination and enrichment of Zn in all the sampled sites. These results suggest a high anthropogenic influence on the heavy metals levels.